\(\dfrac{2}{3}\times\dfrac{4}{5}-\dfrac{1}{3}\times\dfrac{4}{5}=\left(\dfrac{2}{3}-\dfrac{1}{3}\right)\times\dfrac{4}{5}=\dfrac{1}{3}\times\dfrac{4}{5}=\dfrac{4}{15}\)
\(\dfrac{1}{2}:\dfrac{3}{4}+\dfrac{1}{6}:\dfrac{3}{4}=\dfrac{1}{2}\times\dfrac{4}{3}+\dfrac{1}{6}\times\dfrac{4}{3}=\left(\dfrac{1}{2}+\dfrac{1}{6}\right)\times\dfrac{4}{3}=\dfrac{2}{3}\times\dfrac{4}{3}=\dfrac{8}{9}\)
\(\dfrac{1}{2}:\dfrac{3}{4}-\dfrac{1}{6}:\dfrac{3}{4}=\dfrac{1}{2}\times\dfrac{4}{3}-\dfrac{1}{6}\times\dfrac{4}{3}=\left(\dfrac{1}{2}-\dfrac{1}{6}\right)\times\dfrac{4}{3}=\dfrac{1}{3}\times\dfrac{4}{3}=\dfrac{4}{9}\)
a) `2/3 xx 4/5 - 1/3 xx4/5`
`= 4/5(2/3+1/3)`
`= 4/5 xx 1`
`= 4/5`
b) `1/2 : 3/4 + 1/6 : 3/4`
`= 1/2 xx 4/3 + 1/6 xx 4/3`
`= 4/3(3/6+1/6)`
`= 4/3 xx 4/6`
`= 8/9`
c) `1/2 : 3/4 - 1/6 : 3/4`
`= 1/2 xx 4/3 - 1/6 xx 4/3`
`= 4/3(3/6-1/6)`
`= 4/3 xx 2/6`
`= 4/9`